From the Slave Stories to Quilombos in Brazil and the Recognition of the Remnats by the Brazilian Supreme Court - Medeiros, Aurea Bezerra; Neto, Menelick de Carvalho (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The article aims to portray the struggle of black people in search of their rights as a person, as an individual, based on an analysis of slavery in Brazil that ravaged this country for many years.  Another point discussed is the struggle of quilombola communities for recognition and ownership of their lands, a right expressed in the 1988 Constitution, however it is a reality far from being experienced by the 1,782 quilombola communities.